2015
DOI: 10.1007/s10147-015-0892-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extensive intraoperative peritoneal lavage therapy (EIPL) on stage III B + C and cytology-positive gastric cancer patients

Abstract: EIPL therapy combined with complete resection and sufficient (D2) lymphadenectomy could improve the prognosis of CY1/P0 gastric cancer and, to a similar extent, that of stage III B + C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The results of relevant studies suggest that patients with good preoperative therapeutic responses may have a chance to undergo radical surgery, following which their median survival could be extended from 12.6 to up to 43.2 months [134]. The efficacy of preoperative chemotherapy and lymph node involvement are important factors affecting their OS [135, 136]. Another study has reported that CY1 patients treated with HIPEC (paclitaxel used as intraperitoneal perfusion) combined with S-1 and paclitaxel as systemic chemotherapy, providing that their exfoliative cytology changed to negative and they could undergo radical surgery, their OS was observed to increase from 14.3 (without surgery) to 30.5 months (with radical surgery) [137].…”
Section: Comprehensive Treatment Of Gastric Cancermentioning
confidence: 99%
“…The results of relevant studies suggest that patients with good preoperative therapeutic responses may have a chance to undergo radical surgery, following which their median survival could be extended from 12.6 to up to 43.2 months [134]. The efficacy of preoperative chemotherapy and lymph node involvement are important factors affecting their OS [135, 136]. Another study has reported that CY1 patients treated with HIPEC (paclitaxel used as intraperitoneal perfusion) combined with S-1 and paclitaxel as systemic chemotherapy, providing that their exfoliative cytology changed to negative and they could undergo radical surgery, their OS was observed to increase from 14.3 (without surgery) to 30.5 months (with radical surgery) [137].…”
Section: Comprehensive Treatment Of Gastric Cancermentioning
confidence: 99%
“…The presence or absence of ascitic fluid was documented and ascitic fluid or peritoneal lavage were analyzed by cytological examination. Extensive intraperitoneal lavage (EIPL) was performed with 10 L of saline after draining all the ascitic fluid (if present) [32]. Neoadjuvant laparoscopic HIPEC was then performed with oxaliplatin 200 mg/m 2 in 4-5 L of saline solution at 43 • C for 60 min.…”
Section: Neoadjuvant Laparoscopic Hipecmentioning
confidence: 99%
“…Before and after CRS, extended intraperitoneal lavage (EIPL) with 10 L of physiologic saline solution was routinely carried out in all cases undergoing CRS [32]. For HIPEC, 4-5 L of heated saline were instilled in the peritoneal cavity with either mitomycin C 20 mg/m 2 with cisplatin 40 mg/m 2 or oxaliplatin 200 mg/m 2 with 5-fluorouracil 500 mg/m 2 .…”
Section: Treatment and Follow-up Protocolmentioning
confidence: 99%